Islamic Legal Perspectives on Niqab-Wearing Women who use Makeup - Hidayat, Rahmat; Nulhakim, Naufal Allam; Muhibban (ALFATWA jurnal tentang hukum dan syariat, 2025)
The phenomenon of niqab-wearing women using makeup has sparked various perspectives within Islamic law, both from the standpoint of fiqh and prevailing social norms. This study aims to explore Islamic legal views on the use of makeup by niqab-wearing women by considering diverse scholarly opinions and the social implications of the practice. A qualitative research method was employed, utilizing a literature-based approach that includes analysis of classical fiqh texts, contemporary fatwas, and relevant academic articles. The findings reveal differing opinions among Islamic scholars regarding the permissibility of makeup use by women who wear the niqab. These differences are influenced by factors such as the extent of makeup application, the intended purpose behind its use, and the surrounding social context. Some scholars permit the use of makeup under the condition that it is not excessive and is not intended to attract non-mahram attention, while others view it as contradictory to the fundamental purpose of the niqab, which is to serve as a means of protection from the male gaze. Accordingly, this study concludes that the ruling on makeup use among niqab-wearing women is a matter of ijtihād, subject to interpretation by different schools of thought and cultural dynamics within each society